Complex magnetic order from multiple Ce-sites in Ce3Pd4Sn6. (28th June 2017) - Scheidt, E-W; Fischer, A; Wybranski, O; Eickerling, G; Scherer, W; Baenitz, M; Mayr, F; Heying, B; Pöttgen, R
Abstract: Polycrystalline C e 3 P d 4 S n 6 samples were synthesized by arc-melting and subsequent annealing at 970 K. Specific heat, electrical resistivity and magnetic susceptibility measurements are performed over a wide range in temperature and provide hints for the presence of a complex magnetic ordering below 3 K arising from three crystallographically independent Ce sites. This behaviour is driven by a complex interplay between ferro-, ferri-, and antiferromagnetic correlations among the Ce atoms.